Fresh Milk Quality Analysis of Buffalo, Cow, Goat and Sheep of Sunwal Municipality (West), Nepal - Shrestha, Deepak Kumar (Curriculum Development Journal, 2021)
In the present study, the fresh raw milk of four different mammals viz, buffalo, goat, cow and sheep were collected from village area of Sunwal Municipality and analyzed for their physio-chemical parameters viz, moisture, conductivity, pH, titratable acidity specific gravity, fat solids not fat and total solid. It was found that all measured parameters were found as per recommended standard as compared with reported nutritional quality of milk from WHO standards and other International Standards. The main objective of this study was to compare the physio-chemical properties and quality parameters of different fresh milk samples available in Sunwal Municipality, Nawalparasi (West), Nepal and provide nutritional benefits for health. These tests were carried in chemistry laboratory of Butwal Multiple Campus and Dairy Devlopment Corporation in Butwal industrial area. The value of pH ranged from 6.58±0.53 to 6.65±0.51, conductivity ranged from 6.52±1.98 to 10.8±2.07 mS, moisture content ranged from 78.1±4.30% to 89.7±5.02% .Similarly TTA% ranged averagely from 0.117% to 0.153%,CLR from 26.1 to 28.3, specific gravity ranged from1.0261 to 1.0283 averagely and fat % ranged from 3.3±0.41% to 6.8±0.96%. Similarly, SNF% ranged from 1.58±0.49% to 2.05±0.22% and TS% ranged from 11.225±0.28% to 16.075±1.19 % respectively.